KAJIAN KENYAMANAN DAN KEAMANAN WISATAWAN DI KAWASAN PARIWISATA KUTA LOMBOK - Wahyu Khalik (JURNAL MASTER PARIWISATA, 2014)
Comfort and security are vital factors in tourism destination of Kuta Lombok with great tourism potential. However, this potential will not be desirable if the conditions are not created by comfort and security. This proves that there are factors that affect the comfort, community understanding of tourism awareness, and community participation in comfort and security of tourists. The study was conducted aimed to determine the factors that affect comfort and safety, the level of community understanding of tourism awareness, and community participation in the comfort and security of tourists in Kuta Lombok tourism.This study examines the comfort and safety of tourists in tourism of Kuta Lombok are included in the descriptive study. Therefore, the research conducted through a qualitative approach. Methods of data collection through observation, interview and documentation. Decision is determined by the method of purposive, with 15 informants. The theory applied is the theory of structural functionalism which analyzed the factors and community participation, and motivation theory is applied to analyze the level of community understanding about tourism awareness.The analysis results of research conducted by qualitative descriptive analysis presents the results of research through a narrative supported by photographs. The results of this study suggests that the comfort and safety factor is  influenced by the low level of community understanding in the elements of tourism awareness through Sapta Pesona. The low raises community understanding of factors that affect comfort and safety as a factor of environmental aspects of parking management and environmental hygiene, factors of economic activity and the hawkers aspects trasnportation service providers as well as factors in the aspect of tourism access roads were damaged. Community participation in the comfort and security of tourists is not functioning optimally. This is caused by unsynchronization between organizations. Forms of community participation in the form of the participation into the organization and the coast guard and empowerment of communities in the festival. Based on those results of the three studies, the government of Central Lombok is expected especially for Culture and Tourism Department particular attention to the factors that affect comfort and safety, and the formation of tourism awareness with benchmarks Sapta Pesona.